2009
DOI: 10.1007/s11135-009-9250-y
|View full text |Cite
|
Sign up to set email alerts
|

Firm leverage and investment decisions in an emerging market

Abstract: Leverage, Investment, Panel data, Emerging markets,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…Butnotably in our study, it is found that cash flows have no significant influence on investment even though the sign of the coefficients is positive. Our findings are in line with previous studies (Lang et al, 1996;Aivazian et al, 2005;Odit andChittoo, 2008;Umutlu, 2010;Kannadhasan, 2014).…”
Section: Influence Of Leverage and Growth Opportunities On Investmentsupporting
confidence: 94%
See 2 more Smart Citations
“…Butnotably in our study, it is found that cash flows have no significant influence on investment even though the sign of the coefficients is positive. Our findings are in line with previous studies (Lang et al, 1996;Aivazian et al, 2005;Odit andChittoo, 2008;Umutlu, 2010;Kannadhasan, 2014).…”
Section: Influence Of Leverage and Growth Opportunities On Investmentsupporting
confidence: 94%
“…At the company level, debt has both positive and negative implications. Debt component of financial structure safeguards from tax and increases the valuation of the firm but at the same time creates the problem of bankruptcy (Grossman and Hart, 1982;Umutlu, 2010).Proliferation in leverage ratio has negative impact on stock price of the firm as higher leverage ratio constrains the firm in getting more funds and restricts the future investment prospects. The adverse association between leverage and stock prices is strong in highly leveraged firms as compared to low leveraged firms, as latter face higher default risk.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…On average, this literature shows that stock price positively impacts firms' investment levels. Some of these papers include Aivazian et al (2005), Hanazaki and Liu (2007), Yuan and Motohashi (2008), Bokpin and Onumah (2009), Umutlu (2010), Ma'in and Ismail (2011), Geng and N'Diaye (2012, and Wang et al (2013).…”
Section: The Issue Of Stock Market Liquidity: Literature Reviewmentioning
confidence: 99%
“…(2009) Türkiye'de 2000-2006 döneminde regresyon ve korelasyon analizi kullanarak yapmış oldukları çalışmada, kaldıracın firma yatırımları üzerinde negatif etkiye sahip olduğunu, düşük büyüme fırsatlarına sahip firmalarda ilişkinin istatistiksel olarak anlamlı olduğunu ifade etmişlerdir. Umutlu (2010) Türkiye'de 1993-2002 döneminde tek yönlü hata bileşen modeline göre sadece düşük büyüme fırsatlarına sahip olan firmalarda kaldıracın yatırımlar üzerinde etkili olduğunu, iki yönlü hata bileşen modeline göre ise bu ilişkinin kaybolduğunu ifade etmişti. Bao (2010), Çin'deki iki sermaye piyasasına kayıtlı firmalar üzerinde 1992-2009 yılları verilerini kullanarak yaptığı OLS analizleri sonucunda, tüm firmalar baz alındığında finansal kaldıraç ve yatırım ilişkisinin istatistiki olarak anlamlı ve negatif olduğunu ortaya koyarken, sektörler arasında ayrıştırma yapıldığında, imalat, ticaret ve finans sektörü için söz konusu ilişkinin istatistiki olarak anlamlı olmadığını ifade etmiştir.…”
Section: Li̇teratür Taramasiunclassified